Pengaruh Daya Tarik Wisata dan Media Sosial Instagram terhadap Keputusan Berkunjung Wisatawan Generasi Z di Samalengoh Camp Kabupaten Sumedang - Triana, Anisa; Nurjamilah, Nurjamilah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze in depth the influence of Tourist Attractions and Instagram Social Media on the Visiting Decision of Generation Z tourists to Samalengoh Camp, Sumedang Regency. In this research, the author used quantitative research and survey methods. A total of 96 visitors were sampled using non-probability sampling techniques. The results of the study are as follows: 1) Tourist Attractions and Instagram Social Media significantly influence the visiting decision of Generation Z tourists to Samalengoh Camp simultaneously; 2) Tourist Attractions significantly influence the visiting decision of Generation Z tourists to Samalengoh Camp partially; 3) Instagram Social Media significantly influence the visiting decision of Generation Z tourists to Samalengoh Camp partially.